(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This study was carried out to investigate the toxicological effects of four brands of mosquito incense stick smoke (DR insecticide stick (AS-1987), Incense upgraded formula (BM-102), Fragrance (B3-254) and Citronella (A7-435) on selected biochemical and histological profile of male albino wistar rats. Fifteen (15) wistar rats with mean weight (174.6 Â±0.91g) were randomly divided into five (5) groups. Group I were considered as negative control while group II, III, IV and V were challenged with the brands of mosquito incense stick smoke for 8 hours daily by inhalation for 21 days. Laboratory investigations were carried out using standard protocols. It was observed that the activities of the liver enzymes (Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST) and Alkaline Phosphatase (ALP) increased significantly (p<0.05) in all the experimental rats when compared with the control. The histopathological alterations examined in the liver tissues of the experimental rats during the study period include mild necrosis, mild degeneration of hepatocytes and cellular infiltration from group III, IV and V respectively. Lung tissues of the challenged rats of group II, III and V revealed mild cellular infilterations around alveolar septa, hyperplasia and bronchiolar epithelial wall degeneration respectively. Kidney tissues revealed glomeruli distortion, mild haemorrhage and renal damage from group III and IV respectively. The alterations examined in the liver, kidney and lung tissues of the experiment rats were period dependent but independent of mosquito sticks brands which inferred that continuous exposure to mosquito stick